The Determinants of Profitability in Village Credit Institution - Putu Diah Kumalasari; Ni Putu Lisa Ernawatiningsih (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2020)
This study aimed to determine the effect of the growth of saving deposit, time deposit, and credit on profitability in village credit institution. 15 village credit institutions were taken as samples, and later tested statistically by using the multiple linear regression analysis. The results suggested that the growth of saving deposit and credit had no effect on profitability, while the growth of time deposit had positive effect on profitability. This study is expected to add insight into profitability, especially regarding the determintans of profitability.